Costs and cost-effectiveness of malaria reactive case detection using loop-mediated isothermal amplification compared to microscopy in the low transmission setting of Aceh Province, Indonesia - Zelman, BW; Baral, R; Zarlinda, I; Coutrier, FN; Sanders, KC; Cotter, C; Herdiana, H; Greenhouse, B; Shretta, R; Gosling, RD; Hsiang, MS (BMC, 2018)
Background Reactive case detection (RACD) is an active case finding strategy where households and neighbours of a passively identified case (index case) are screened to identify and treat additional malaria infections with the goal of gathering surveillance information and potentially reducing further transmission. Although it is widely considered a key strategy in low burden settings, little is known about the costs and the cost-effectiveness of different diagnostic methods used for RACD. The aims of this study were to measure the cost of conducting RACD and compare the cost-effectiveness of microscopy to the more sensitive diagnostic method loop-mediated isothermal amplification (LAMP).